The 2022 World Health Organization Classification of Tumours of the Urinary System and Male Genital Organs—Part A: Renal, Penile, and Testicular Tumours - Moch, Holger; Amin, Mahul B.; Berney, Daniel M.; Compérat, Eva M.; Gill, Anthony J.; Hartmann, Arndt; Menon, Santosh; Raspollini, Maria R.; Rubin, Mark A.; Srigley, John R.; Hoon Tan, Puay; Tickoo, Satish K.; et al. (European urology, 2022)
The 2022 World Health Organization classification contains new renal tumour entities. Some of them are based on a molecular driver event. The classification of penile squamous cell carcinomas is simplified and based on the presence of human papillomavirus. A new chapter with tumours of the scrotum has been introduced. Nomenclature changes of testicular tumours include replacement of the term “primitive neuroectodermal tumour” by “embryonic neuroectodermal tumour”. The term “carcinoid” has been changed to “neuroendocrine tumour”. The fifth edition of the World Health Organization (WHO) classification of urogenital tumours (WHO “Blue Book”), published in 2022, contains significant revisions. This review summarises the most relevant changes for renal, penile, and testicular tumours. In keeping with other volumes in the fifth edition series, the WHO classification of urogenital tumours follows a hierarchical classification and lists tumours by site, category, family, and type. The section “essential and desirable diagnostic criteria” included in the WHO fifth edition represents morphologic diagnostic criteria, combined with immunohistochemistry and relevant molecular tests. The global introduction of massive parallel sequencing will result in a diagnostic shift from morphology to molecular analyses. Therefore, a molecular-driven renal tumour classification has been introduced, taking recent discoveries in renal tumour genomics into account. Such novel molecularly defined epithelial renal tumours include SMARCB1-deficient medullary renal cell carcinoma (RCC), TFEB-altered RCC, Alk-rearranged RCC, and ELOC-mutated RCC. Eosinophilic solid and cystic RCC is a novel morphologically defined RCC entity. The diverse morphologic patterns of penile squamous cell carcinomas are grouped as human papillomavirus (HPV) associated and HPV independent, and there is an attempt to simplify the morphologic classification. A new chapter with tumours of the scrotum has been introduced. The main nomenclature of testicular tumours is retained, including the use of the term “germ cell neoplasia in situ” (GCNIS) for the preneoplastic lesion of most germ cell tumours and division from those not derived from GCNIS. Nomenclature changes include replacement of the term “primitive neuroectodermal tumour” by “embryonic neuroectodermal tumour” to separate these tumours clearly from Ewing sarcoma. The term “carcinoid” has been changed to “neuroendocrine tumour”, with most examples in the testis now classified as “prepubertal type testicular neuroendocrine tumour”.